The effect of glutamine and maltodextrin acute supplementation on anaerobic power - Khorshidi-Hosseini, M.; Nakhostin-Roohi, B. (Asian Journal of Sports Medicine, 2013)
Purpose: The aim of this study was to investigate whether supplementation of carbohydrate together with peptide glutamine would prevent anaerobic power decrease during repeated competitions.